Direct Conversion Front End for LTE and LTE-A with Frequency-Translational Feedback, Harmonic Rejection Mixer and Input Matching Compensation - Andersson Hägglund,Douglas (2016)
This thesis covers the design of a wideband, flexible front end for LTE and LTE-A in a 65 nm CMOS process. A topology with global frequency translational feedback is investigated and a harmonic rejection mixer is implemented. To compensate for parasitics at the RF input, a variable phase shift is used in the global feedback to improve input matching and prevent loss of noise performance. Combinations of these techniques are compared to a standard quadrature implementation. The suitability of three different baseband amplifiers for the circuit is also evaluated. The full system is functional between 700 MHz and 3.7 GHz and has a noise figure of between 1.5 and 1.3 dB depending on frequency of operation. The system provides 43 dB of gain and has an out-of-band IIP3 and CP1dB of -8 and -23 dBm, respectively. The current consumption is 21 mA from a 1.2 V supply and includes the consumption of the LNTA and baseband amplifiers.